VD_FINDINFO HC / 2011 / 134 vom 12. Januar 2011 - VD Tribunal cantonal (2011)
ACTION EN PAIEMENT D'ENTRETIEN, ENFANT, MINORITÉ{ÂGE}, MAJORITÉ{ÂGE}, REVENU HYPOTHÉTIQUE, DROIT ÉTRANGER | 280 al. 2 CC, 451 ch. 3 CPC, 405 al. 1 CPC (CH)